Pemetaan Genangan Banjir Daerah Aliran Sungai Way Tipo Kabupaten Tengah Menggunakan Aplikasi HEC-RAS - Noviani, Erina; Dyah Indriana Kusumastuti; Aprizal (Universitas Nahdlatul Ulama Blitar, 2025)
Flooding is a recurring issue in the Way Tipo Watershed (DAS), impacting both the environment and surrounding communities. This study analyzes flood inundation areas using a quantitative approach based on hydrology and hydraulics, employing HEC-RAS modeling. The flood discharge was calculated using the Nakayashu method, yielding return period discharges (Q2–Q100) ranging from 744.46 to 993.05 m³/s. Simulation validation with the design discharge Q25 and Q50 at 988.82 m³/s resulted in an inundation area of 76.29 km². The analysis of the relationship between discharge and inundation area using Excel produced an equation with R² > 0.94, indicating a strong correlation. The findings of this study can serve as a basis for flood mitigation planning and sustainable watershed management. The implication of these findings is that the mathematical model obtained is capable of providing a fairly accurate picture of potential flooding based on water discharge, thereby assisting policymakers, local governments, and relevant parties in formulating flood prevention strategies, determining flood-prone zones, and spatial planning for the region.